Analysis of the Implementation of Project-Based Learning Integrated with Javanese Culture in Enhancing Teachers' Professional Competence for Quality Education - Oktiana Handini; Sawitri; Taufik Nur M (CV Kalimasada Group, 2026)
Purpose – This study investigates the implementation of Project-Based Learning (PjBL) integrated with Javanese cultural values and its impact on enhancing teachers' professional competence and achieving quality education. Design/Methodology/Approach – A descriptive qualitative approach was employed. Data were collected through classroom observations, in-depth semi-structured interviews with 12 teachers from three schools in Surakarta and Sukoharjo, and document analysis. Thematic analysis following Braun and Clarke’s (2006) framework was used, supported by triangulation and member checking. Findings – Integrating Javanese principles -Gotong Royong, Unggah-Unggah, and Tepa Selira- into PjBL significantly enhanced teachers’ pedagogical, professional, social, and personal competencies. Student cognitive scores improved from an average of 47 (pre-test) to 86 (post-test). The approach fostered higher engagement, motivation, and character development aligned with the Pancasila student profile. It was perceived as substantially more effective than traditional methods in creating meaningful, context-specific learning. Originality/Value – : This study provides novel insights into culturally responsive PjBL by embedding specific Javanese local wisdom into the Gold Standard PBL framework. It offers practical implications for teacher professional development and curriculum design rooted in indigenous values.